Un estudio teórico de la estructura electrónica y las propiedades dieléctricas de B-Nb2O5 (2011)
ABSTRACT: In this work we have investigated theoretically the electronic and optical properties of niobium-oxide Nb2O5 for one of its crystalline phases, namely the B-phase. We have used Density Functional Theory along with the Generalized Gradient Approximation with one of its new modified functional targeted for solids: PBEsol. The calculated band gap is indirect (Eg=2,54 eV), with the valence band maximum located at and the conduction band minimum located at ( 1/3,1/3,1/3). We present also the calculated real and imaginary part of the dielectric tensor, the index of refraction, the reflectivity, the transmittance and the real part of the optical conductivity. The calculated value of the index of refraction is 2,52, which is in good agreement with the experimental value of 2,64.